1996
DOI: 10.1046/j.1365-2249.1996.d01-764.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mucocutaneous candidiasis. I. Altered antigen-stimulated IL-2, IL-4, IL-6 and interferon-gamma (IFN-γ) production

Abstract: SUMMARYPatients with chronic mucocutaneous candidiasis (CMC) present with persistent infections with the opportunistic yeast Candida. Impaired cell-mediated responses to Candida have been documented in CMC patients, but the defect remains poorly understood. The importance of Th1 cytokines in resistance and Th2 in susceptibility to Candida infections has recently been demonstrated in murine models. In our studies we evaluated production of IL-2 and IFN-°(markers of Th1 type responses) as well as IL-4 and IL-6 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
2
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 20 publications
2
31
2
4
Order By: Relevance
“…Our results demonstrate that although CMC patients produced high levels of antibodies, there were subtle differences in class and subclass of specific antibody produced to all tested antigens (CAg, PPS and TT), which are most pronounced in children. This may relate to altered cytokine production previously shown in these patients [10].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our results demonstrate that although CMC patients produced high levels of antibodies, there were subtle differences in class and subclass of specific antibody produced to all tested antigens (CAg, PPS and TT), which are most pronounced in children. This may relate to altered cytokine production previously shown in these patients [10].…”
Section: Introductionmentioning
confidence: 70%
“…However, high levels of IgA antibodies in CMCa to TT and PPS as well are more difficult to explain. As transforming growth factor-beta (TGF-) has been shown to induce switching of activated B cells to IgA production, levels of this cytokine in CMC patients warrant further study [14], particularly in view of our previous findings of imbalanced production of other cytokines [10].…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the primary immunological defect in HIE has remained elusive, recent findings indicate a profound impairment in the regulation of interleukin 4 (IL-4)-dependent IgE production, 2 confirming previously published data showing defective interferon gamma (IFN␥) production. 3 This pattern, however, seems not to be specific as it has been shown in chronic mucocutaneous candidiasis, 4 another rare primary immunodeficiency of unknown aetiology. The mainstay of conventional management in HIE is aggressive antibiotic treatment and prophylaxis targeting Staphylococcus aureus, the known main pathogen in these patients.…”
mentioning
confidence: 96%
“…However, it is not known whether T cells themselves are impaired or whether the defect(s) affects regulators and/or mediators of T-cell activity, such as cytokines. Recent preliminary data demonstrated that patients with CMC had an altered pattern of cytokine production in response to Candida antigens, with low or no IL-2 production, increased IL-6 production, and markedly high titers of immunoglobulin G1 (IgG1) and IgA Candida-specific antibodies consistent with a low type 1 (Th1) and high type 2 (Th2) cytokine production pattern (16,17). These preliminary results also demonstrated that the differences in the responses depended on the type of Candida fraction used (e.g., protein-or carbohydrate [CHO]-rich fraction) (17).…”
mentioning
confidence: 99%
“…Recent preliminary data demonstrated that patients with CMC had an altered pattern of cytokine production in response to Candida antigens, with low or no IL-2 production, increased IL-6 production, and markedly high titers of immunoglobulin G1 (IgG1) and IgA Candida-specific antibodies consistent with a low type 1 (Th1) and high type 2 (Th2) cytokine production pattern (16,17). These preliminary results also demonstrated that the differences in the responses depended on the type of Candida fraction used (e.g., protein-or carbohydrate [CHO]-rich fraction) (17). In this paper we present results of studies of a cohort of CMC patients in which we looked at their ability to respond to stimulation with various CHO-or protein-rich fractions of Candida albicans, as well as non-Candida antigens, by producing a wide range of cytokines that play a role in mediating T-cell activation, including inflammatory cytokines (IL-6, tumor necrosis factor alpha [TNF-␣]), anti-inflammatory cytokines (IL-10), and type 1 and type 1-inducing cytokines (IL-2, IFN-␥, IL-12), as well as type 2 cytokines (IL-4, IL-5).…”
mentioning
confidence: 99%